2008
DOI: 10.1016/j.ejrad.2008.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of non-linear blending in dual-energy computed tomography

Abstract: Dual-energy CT scanning has significant potential for disease identification and classification. However, it dramatically increases the amount of data collected and therefore impacts the clinical workflow. One way to simplify image review is to fuse CT datasets of different tube energies into a unique blended dataset with desirable properties.A non-linear blending method based on a modified sigmoid function was compared to a standard 0.3 linear blending method. The methods were evaluated in both a liver phanto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…In general, DE CT is performed by acquiring projection data with two different x-ray beam spectra. A number of different image types can be generated from the resulting data, including images corresponding to the low- and high-energy spectra, mixed images that represent a linear or nonlinear blending of the low- and high-energy images, material-specific images, and virtual monoenergetic images (17–20). …”
mentioning
confidence: 99%
“…In general, DE CT is performed by acquiring projection data with two different x-ray beam spectra. A number of different image types can be generated from the resulting data, including images corresponding to the low- and high-energy spectra, mixed images that represent a linear or nonlinear blending of the low- and high-energy images, material-specific images, and virtual monoenergetic images (17–20). …”
mentioning
confidence: 99%
“…In particular, the high-intensity regions corresponding to iodine contrast-enhancement are preferentially extracted by 80-kVp data, to maintain the high image contrast in regions of high iodine concentration. By contrast, low-intensity levels, which correspond to air, water, and soft tissues, are less noisy in 140-kV scan and should be preferred in the blending process [49,50]. The result is an image in which iodine signal is magnified, while optimizing contrast differences and minimizing image noise.…”
Section: Spectral Ct: Study Protocols and Clinical Applicationsmentioning
confidence: 97%
“…The 80 and 140 kV datasets were blended using the moidal blending function. Every combination of moidal level and width was applied to the data, and the CNR was calculated using the method from [8].…”
Section: Cnr Calculationmentioning
confidence: 99%
“…A review of several of these functions can be found in [7]. One approach, a modified sigmoid blending referred to as "Moidal Blending," was viewed favorably by radiologists in [8]. The moidal blending function, shown in Figure 1, requires two parameters.…”
Section: Introductionmentioning
confidence: 98%